Own gol: impact of soccer matches on domestic violence in Brazil - Arabe, Isadora Bousquat (2022)
Domestic violence (DV) is the most common form of violence against women (VAW) and is a major public health issue. Eliminating such violence is a key objective of the sustainable development goals. Some theories investigate the importance of emotional cues or visceral factors in eliciting DV. This paper examines the link between emotional shocks induced by unexpected soccer results and domestic violence (DV) in Brazil. To establish the unanticipated results, we analyzed data from the pregame betting markets of 3,800 match results of Brazils primary football competition, Campeonato Brasileiro, from 2015 to 2019. We ar- gue that the risk of DV incidents can be affected by the gain-loss utility of soccer games around a rationally expected reference point. Our analysis focuses on two major states of Brazil: Rio de Janeiro and Sao Paulo, and we use two quantifiable measures of daily occurrences of DV: calls to a domestic violence helpline, Ligue 180, and police reports from 2015 to 2019. Our results indicate that an increase of one standard deviation (SD) in the number of people experiencing a negative emo- tional shock as a result of the outcomes of soccer matches increases the expected number of DV-related police reports after the match by approximately 7.6%. We found no impact when we use our other source of DV data, calls to a domestic violence helpline. We found a significant impact of games with opponents from the same city that take place from Monday through Friday; an increase of one SD in the negative emotional shock increases the expected numbers of DV police reports by 66%, and increases calls to the Ligue 180 helpline by 41%.